Mineralogical characterization of the flotation products using automated mineral liberation analysis at the Erdenetiin Ovoo Cu-Mo porphyry deposit, Mongolia - Tumen-Ayush, Batmunkh; Bavuu, Chinzorig; Adiyasuren, Narangerel; Davaajav, Ganbileg; Batbileg, Davaadulam; Ganbat, Sondor; Tserendagva, Tsend-Ayush; Dorjyunden, Altankhuyag; Chimed, Ganzorig (Mongolian Geoscientist, 2025)
The flotation process is used to extract copper-molybdenum sulfide minerals from ore. The selection of the flotation technology scheme largely depends on factors such as the composition of sulfide ore in the ore body, grain size, and characteristics of the ore mineral association. The chemical and mineralogical analysis of flotation products was collected from the Erdenetiin Ovoo Cu-Mo porphyry deposit. The deposit is the largest porphyry copper-molybdenum deposit in Mongolia. The aim of this study was to demonstrate the occurrence mechanism of copper minerals in flotation tailing using the fully automated Tescan Integrated Mineral Analyzer. The chemical analysis of the flotation products (feed, concentrates and tailings) sample was conducted by X-ray fluorescence, and the mineralogical composition of the flotation feed sample was characterized using X-ray diffraction. The copper content of the flotation tailing was 0.024%. Mineralogical characterization results showed that almost all copper minerals occurred within coarse gangue particles, the primary and secondary copper minerals were accumulated in the size fractions less than 150 μm and 13.5 μm, respectively. The finest grain size distribution was observed in secondary copper particles of size -19 μm. Chalcopyrite was the main copper-bearing mineral, and it was closely associated with K-feldspar and silicate in the flotation tailings. The flotation tailing sample still contained 24.1 wt% liberated primary copper (chalcopyrite) and 24.13 wt% secondary copper due to their extremely fine grain size particle. The mineral map derived from Tescan Integrated Mineral Analyzer analysis revealed that copper minerals mainly occurred as finely disseminated and fully enclosed structures within gangue minerals.